STUDI PENGEMBANGAN OBJEK WISATA PULAU HOGA DAN PENYERAPAN TENAGA KERJA DI KECAMATAN KALEDUPA KABUPATEN WAKATOBI - Hasriani, Hasriani; Rafiy, Muh.; Ahmad, Sabir (JURNAL EKONOMI UHO, 2016)
The purpose of this research is to analyze impact of tourism object on employment absorption and local income in  Kaledupa District Wakatobi Regency. Data obtained from Wallacea Operation Office and Local Gowerment of Wakatobi Regency. The data consists: labor, tourists, tourism facilities, infrastructure and local income. Data analyzed through descriptive. The results showed that development Hoga of Island in Kaledupa Distric improve employment opportunity, increase in income of society and  contribute on Local Income. The  local goverment income experience  average rates of growth  about 2,07 percent.